Profile of Cerebral Arteriovenous Malformations at Dr. Saiful Anwar Hospital Malang: A Multi-Modality Epidemiologic Study - Setyawan, Agung; Imron, Fatkhul Ali (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Brain arteriovenous malformations (AVMs) are congenital abnormalities in which direct connections form between arteries and veins, bypassing the capillary network and resulting in significant hemodynamic disturbances. This abnormal vascular architecture increases the risk of life-threatening intracranial hemorrhage. The diagnosis and management of brain AVMs are challenging due to their variability in size, location, and vascular supply. Accurate assessment requires advanced imaging modalities such as CT, MRI, and DSA, combined with the Spetzler-Martin (S-M) classification for risk stratification. Epidemiological studies are important for guiding clinical decisions. This study aims to describe the demographic, clinical characteristics, and imaging findings of brain AVMs patients at Dr. Saiful Anwar Hospital, Malang. Material and Methods: A retrospective descriptive study using radiology records from September 2020 to August 2024, including all patients diagnosed with brain AVMs who underwent CT, MRI, or DSA imaging. Results: The majority of patients were male (69.6%), and the largest age group was ≥50 years (36.9%). The most common presenting symptom was neurological deficit (47.8%), followed by headache (30.4%) and seizure (21.8%). S-M grading varied by imaging modality, CT most frequently detected grade III, MRI identified grades III–V, while DSA most often revealed grade I. Conclusion: Cerebral AVMs are more commonly treated in males and individuals aged ≥50 years. The main symptoms are neurological deficits, headaches, and seizures. A multimodal approach is essential for diagnosis and management.